Strategic Development Planning for Global Integration: A Comprehensive Framework for State Universities in the Philippines - Armas, Kenneth L.; Jugo, Rhodora R. (International Review of Management and Marketing, 2024)
This study develops a comprehensive strategic development plan for a state university in the Philippines, aligning its vision, mission, and goals with current trends, internal and external factors, and global objectives. Utilizing a qualitative research design, the study integrates environmental analysis tools such as SWOT and PESTLE, alongside an extensive stakeholder consultation process involving students, faculty, alumni, non-academic personnel, industry representatives, community partners, and government agencies. The inclusion of stakeholder perspectives was crucial in refining the strategic goals and ensuring that the plan addresses the diverse needs of the university community. The resulting strategic framework emphasizes key themes such as globalization, digital transformation, equity and inclusion, human capital development, research and innovation, and sustainability. This study highlights the importance of a participatory and adaptive approach to strategic planning in higher education, providing a model for institutions seeking to navigate the complexities of the global educational landscape.